Back Cover: Structural, Magnetic and DFT studies on a Charge‐Transfer Salt of a Tetrathiafulvalenepyridyl‐(1, 5‐diisopropyl) verdazyl Diradical Cation (ChemPlusChem 11/2015). Issue 11 (12th October 2015) - Venneri, Shari; Wilson, Justin; Rawson, Jeremy M.; Pilkington, Melanie
Abstract : The cover picture shows a 2:1 charge transfer complex formed from a tetrathiafulvalene (TTF)–pyridylverdazyldiradical cation and tetracyanoquinonedimethane (TCNQ) which crystallizes in a mixed‐stack arrangement. These building blocks show promise for the development of spintronic devices where the spin of the electrons as well as their charge can be used to process information. More details can be found in the Full Paper by Melanie Pilkington et al. onpage 1624 in Issue 11, 2015 (DOI:10.1002/cplu.201500309 ).